Comparative Evaluation of Ketoprofen Gel Alone and in Combination with Doxycycline Gel as Local Drug Delivery in the Treatment of Chronic Periodontitis among Smokers and Non-Smokers: A Randomized Clinical Trial - Krupali J. Gandhi; Priyadarshini P. Nadig; Shivlal Vishnoi; Bhumika S. Sheth; Jinal Desai; Kandarp Raj (Journal of Pharmacy and Bioallied Sciences)
Background and Objective: Often, the treatment goals for chronic periodontitis in smokers are not achieved only by scaling and root planing (SRP) as non-surgical periodontal therapy. Adjunctive therapy such as local drug delivery (LDD) can be carried out in an attempt to reduce the need for periodontal surgery. The study was carried out to determine the efficacy of subgingivally delivered ketoprofen (K) + doxycycline (D) gel and compare it with that of subgingivally delivered ketoprofen (K) gel alone as an adjunct to SRP in smokers and non-smoker patients having chronic periodontitis. Materials and Methods: Twelve patients in the non-smoker group and nine patients in the smoker group having chronic periodontitis with ≥4-mm pocket depth in at least three adjacent teeth in each quadrant were recruited for the study. The quadrants were randomized into K alone and K + D subgroups. 2.5% ketoprofen gel and 2.5% ketoprofen + 3% doxycycline gel were delivered into designated sites after SRP, and the sites were secured using periodontal dressing. Plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD), and relative attachment level (RAL) were recorded at baseline and 3 months. Results: At 3 months follow-up, both the groups showed significant improvement in PI, BOP, PPD, and RAL (P < 0.05). K + D showed a significantly greater reduction of PI, BOP, PPD, and RAL in both smokers and non-smokers than K alone (P < 0.05). Non-smokers responded significantly better than smokers for PI, BOP, PPD, and RAL with both treatment modalities (P < 0.05). Conclusion: The results indicate that smokers and non-smokers demonstrate better clinical outcomes by using K + D LDD as an adjunct to SRP. Moreover, non-smokers responded better to both modalities than smokers.